EVALUASI PASCA HUNI HUNTAP PAGERJURANG DITINJAU DARI ASPEK FUNGSIONAL - Fitri Prawitasari (UNHI Press, 2019)
Pagerjurang permanent shelter or abbreviated as huntap Pagerjurang is one of the permanent shelters that was built in 2012 and it built to fulfill residential needs for Merapi eruption 2010 victims. Huntap Pagerjurang located in Kepuharjo Village, Cangkringan District, Sleman Regency, Yogyakarta Special Province. Huntap Pagerjurang is a mass residences that have a typical building, type 36 and built on an area of 100 mÂ² or on a measuring area 10x10 meters or 8x12.5 meters. Six years after the construction, which were from 2012 until 2018, the typical units will experience changes because of the residents needs or had been damaged. The process used by residents to making building unit comfortable and to fulfill they are needs will be different. The relationship between building unit and residents behavior causes an evaluation of the performance of building unit in terms of functional aspects. The evaluation process is referred to as Post-Occupational Evaluation (EPH). This study used a qualitative method with a grounded theory approach where data collection is explorative and the data collected tends to be text, object or image, not numbers. The results of the research indicate that the main factors that influence changes made by residents to their occupancy are: (1) the need for daily functions that have not been fulfilled in huntap units such as the kitchen; (2) The need for space functions that can accommodate joint activities both family and community that are usually carried out in their home based such as a spacious terrace and guest room area; (3) The need for space functions that can accommodate the addition of new family members due to the birth of children or married children; (4) The need for space for security functions such as a garage for storing valuable vehicles or equipment; (5) The need for wider, more spacious or sufficient space by developing horizontally and vertically with the addition of building structure construction; (6) The need for space that can be used to support the family economy such as a business room or shop.